Journal of conflict & security law. (Oxford : Oxford University Press, 1996)
The Journal of Conflict & Security Law is a refereed journal aimed at academics, government officials, military lawyers and lawyers working in the area, as well as individuals interested in the areas of arms control law, the law of armed conflict and collective security law. The journal aims to further understanding of each of the specific areas covered, but also aims to promote the study of the interfaces and relations between them.
Formerly titled Journal of armed conflict law.
Description based on online resource; title from home page (viewed on September 28, 2016).
Keywords: War (International law) -- Periodicals; International law -- Periodicals; Pacific settlement of international disputes -- Periodicals; Security, International -- Periodicals